Towards developing economic community development and sustainability model of the Asian clam (Etok) industry in Kelantan, Malaysia - Mohammad Ismail; Y. Mohd Rafi; H. Zulhazman; Z. Mohd Nazri; A. R. M. Rooshiban Merican; E. R. Aweng; A. L. Zul Ariff; M. R. Wan Siti Farizan (AIP Publishing, 2021)
This research examines the business profiling of Asian clam (etok) sellers in Kelantan, which has been considered as the food heritage of the state. The study was conducted in order to understand a deep insight into business activities as an initial stage for further investigation to develop a sustainable etok business model. These include etok branding, marketing and proposing the new strategy on promoting and sustaining this heritage food. A total of 108 Etok sellers from ten districts in Kelantan which are Gua Musang, Bachok, Kota Bharu, Pasir Mas, Tumpat, Tanah Merah, Machang, Kuala Krai, Pasir Puteh and Jeli involved in the study. The data were analysed using Statistical Package for the Social Sciences (SPSS) version 24. The descriptive study reveals that the majority of respondents (55.6%) involved in the business for more than ten years and inherited (58.4%) from their parents and ancestors. Most of them (84.3%) are running etok business as a full-time employment. Majority of them (71.3%) earned a steady daily profit of approximately RM100.00 or 25.00USD. This signifies that the industry is still viable and provides a substantial income to those involved in the business. Expectantly, this study will pave a way of comprehensive exploration of etok business in proposing better strategy, promoting and sustaining business in the state of Kelantan.